Identification of erosion processes in the soils of the coastal territory of lake Kandrykul (Republic of Bashkortostan); Известия Томского политехнического университета [Известия ТПУ]. Инжиниринг георесурсов; Т. 336, № 2 - Fattakhova L. A. Leysan Aydarovna (2025, 2025)
Relevance. The change of certain environmental factors (water or wind erosion, anthropogenic component) leads to changes of the structure and properties of the soil body. Coastal area soil can already be affected by erosion, which can also negatively affect the quality of water, because washout of the soil particles from the organic-rich upper part of the soil profile can lead to an acceleration of eutrophication processes. Moreover, the recreational activity of these territories increases the anthropogenic load on the soil cover, thereby aggravating soil degradation. That is why the importance of a comprehensive study of the soil disturbance problems caused by erosion and anthropogenic factors is beyond doubt. Aim. To analyze the behavior of the magnetic and humus profiles during soil cover degradation due to water erosion. Object. Soil profiles of the coastal area of Lake Kandrykul (Republic of Bashkortostan). Materials and methods. Magnetic susceptibility was measured using MFK-1A Kappabridge (AGICO). The hysteresis parameters of the studied sedimentary deposits were determined using a coercive spectrometer (J_meter), the Tyurin method was used to determine the level of humus in the soil. Results. According to the magnetic susceptibility data, the studied soil profiles can be divided into accumulative (soil profiles 2, 6, 7, 10) and eluvial-illuvial (soil profiles 1, 3, 4, 8, 9) types of distribution of magnetic components. According to the Day–Dunlop diagram, the magnetic grains of the samples of the studied soil profiles belong to the category of pseudo-domain particles. Conclusions. Studying magnetic susceptibility and humus level helped us to determine soil profiles as accumulative andeluvial type of magnetic components and humus distribution. We proved that the ferromagnetic component makes the main contribution to the magnetic susceptibility. The method of coercive spectrometry has shown that magnetic grains in the studied soil profiles are pseudo-domain particles, which may indicate their pedogenic origin